A Cross-Sectional Study to Assess Capacity of Health Facility Laboratories in Zone One of Afar Regional State, Ethiopia. (8th August 2018) - Genet Akal, Chalachew; Andualem, Tesfaye
Abstract : Role of laboratory service in patient care is well recognized in developed compared to developing countries like Ethiopia where most medical decisions are based on clinical judgment. Laboratory based medical decisions save life and resources. Thus, health facilities (HFs) having capacitated laboratories provide better health care service. Thus, this study assessed capacity of laboratories found in all nine HFs in zone one of Afar region, Ethiopia. Cross-sectional study was conducted from January to May 2015. Data were collected using questioner from medical laboratory professionals (MLPs) and using cheek list from laboratory registration books. Collected data was analyzed using SPSS. Availability of laboratory related national guidelines and standard operating procedure varies among HFs studied. In 42 selected laboratory equipment and materials assessed, their availability shows variations among HFs from 13 (30.2%) to 32 (74.4%). Among different laboratory tests recommended to be performed at health center (HC) level by World Health Organization (WHO), six tests were not performed in all HC laboratories. Moreover, 11 (31.4%) MLPs received in-service training in the past one year. Internal quality control measures were done in 3 (33.3%) laboratories. However, all laboratories were involved in external quality assurance with varied schedules. Specimens after testing and specimen with prolonged transit time were discarded using standard rejection criteria in 8 (88.9%) and 3 (33.3) laboratories, respectively. Study showed that laboratories assessed have good capacities in involving external quality assurance and having proper laboratory test request format. But capacity of laboratories assessed is limited and unsatisfactory in number of laboratory tests performed at HC laboratories, in internal quality control measure implementation, and in getting up-to-date in-service training to staff. Thus, to enhance capacity of laboratories in HC, responsible bodies shall avail basic laboratory materials and equipment, make fair distribution of MLPs, provide up-to-date training, and implement internal quality control measures in laboratories.